RAD6-Mediated transcription-coupled H2B ubiquitylation directly stimulates H3K4 methylation in human cells. - Kim, J; Guermah, M; McGinty, R; Lee, J; Tang, Z; Milne, T; Shilatifard, A; Muir, T; Roeder, R (2009)
H2B ubiquitylation has been implicated in active transcription but is not well understood in mammalian cells. Beyond earlier identification of hBRE1 as the E3 ligase for H2B ubiquitylation in human cells, we now show (1) that hRAD6 serves as the cognate E2-conjugating enzyme; (2) that hRAD6, through direct interaction with hPAF-bound hBRE1, is recruited to transcribed genes and ubiquitylates chromatinized H2B at lysine 120; (3) that hPAF-mediated transcription is required for efficient H2B ubiquitylation as a result of hPAF-dependent recruitment of hBRE1-hRAD6 to the Pol II transcription machinery; (4) that H2B ubiquitylation per se does not affect the level of hPAF-, SII-, and p300-dependent transcription and likely functions downstream; and (5) that H2B ubiquitylation directly stimulates hSET1-dependent H3K4 di- and trimethylation. These studies establish the natural H2B ubiquitylation factors in human cells and also detail the mechanistic basis for H2B ubiquitylation and function during transcription.